An Evaluation of Clinical Learning Experience among Fourth-year Nursing Students of Nueva Ecija University of Science and Technology - George M. Rivera; Thea Irise M. Eugenio; Romar M. Bendiola; Marie Denise M. Esguerra; Kelvin Mark P. Quetua; Danylen Felyze G. Paras; Leinus Karl P. Santiago; Divina B. Ocampo; Zuzette B. Catabona (Proceedings Series on Health & Medical Sciences, 2021)
The clinical learning environment is an essential component of nursing education as it allows students to integrate theory into clinical practice. However, it is considered a critical factor as it may or may not help the student nurses grow and expand their knowledge, skills, and professional attitude. As such, this study described the clinical learning experience of the fourth-year nursing students of Nueva Ecija University of Science and Technology examining the underlying factors that influence the entire learning experience. The study utilized a descriptive – quantitative correlational design and total enumeration as the sampling procedure. The result showed that most of the respondents were in the early adulthood; female; monthly family income is 5,001-10,000, and preferred working in base hospital, operating room; and preferred the morning shift. The core competencies in which the respondents showed enhanced performance and aptitude were legal responsibility, ethico-moral responsibility, and collaboration and team work. The lowest, on the other hand, were personal and professional development, quality improvement, safe and quality nursing care, and research. A significant relationship between the actual age and safe and quality nursing and communication core competencies. A proposed action plan was devised for student nurses to strengthen their research competency.